Performance Analysis of Cluster based Routing Protocol in MANETs - Bansal, Ravi Kumar (My University, 2007)
In the near future, computing environment can be expected based on the recent progresses and advances in computing and communication technologies. Next generation of mobile communications will include both prestigious infrastructured wireless networks and novel infrastructureless mobile ad hoc networks (MANETs). A MANET is a collection of wireless nodes that can dynamically form a network to exchange information without using any pre-existing fixed network infrastructure. The special features of MANET bring this technology great opportunities together with severe challenges. This thesis describes the fundamentals of ad hoc networking by giving its concept, features, and applications of MANET. Some of the technical challenges MANET poses are also presented. The routing protocols meant for wired networks can not be used for mobile ad hoc networks because of the mobility of nodes. The ad hoc routing protocols can be divided into two classes :- table-driven and on-demand. Routing in wireless mobile ad-hoc networks should be time efficient and resource saving. One approach to reduce traffic during the routing process is, to divide the network into clusters. This work mainly focuses on cluster-based routing protocol CBRP) and its comparative analysis with two other on demand routing protocols Adhoc On Demand Distance Vector(AODV) and Dynamic Source Routing (DSR) which do not use cluster based mechanism for routing .The results presented in this thesis illustrate the importance in carefully evaluating and implementing routing protocols when implementing an ad hoc network protocol.
Keywords: Cluster; Routing Protocol